Inventando la civilización occidental - Thomas C. Patterson (Jangwa Pana, 2013)
The idea of "civilization" evokes powerful images. We learned from elementary school onwards that a few ancient peoples, like the Egyptians or Greeks, were civilized and that civilization has finally achieved its highest level of development in the United States and other Western countries. Civilization is beneficial, desirable, and definitely preferable to being uncivilized. After all, it brings technological progress, greater productivity, and higher standards of living to a few. Moreover, civilized people are and refined, wealthier, and happier than their uncivilized predecessors or neighbors. The idea of civilization has always had its boosters and critics. Here, I want to explore the similarities and in the two perspectives